Mastery of gross motor skills in preschool and early elementary school obese children - Khalaj, Nafiseh; Amri, Saidon (Routledge, 2014)
Background: The purpose of this study was to determine the mastery of gross motor skills among preschool and early elementary school obese children; and determine the differences that exist between these two groups. Methods: Instrument TGMD-2 was used to assess gross motor skill performance of all the participants. Total sample size was 160; 80 obese children and 80 normal weight children. The mean age of preschool children was 4.87 (SD: 0.49), and for early elementary school children was 7.34 (SD: 0.63). The methods of analysis were one-way analysis of variance (ANOVA) and descriptive analysis. The alpha level of 0.05 was the criterion for all statistical significance. Results: The findings of this study revealed that there is a significant difference in gross motor skill performance between preschool obese children and early elementary school obese children. Conclusion: Obese children had lower gross motor skill proficiency compared to their normal weight peers. However, early elementary school obese children (aged between 6 and 8 years) performed poorer gross motor skills compared to preschool obese children (aged between 4 and 6 years).